The Influence of Assignment Methods and Learning Behavior on Student Learning Outcomes - Suleman Suleman; Sri Wahyuni Antu; Salma Malanua (Newinera Publisher, 2022)
This study aims to determine: (1) Differences in science learning outcomes for students who are given assignments individually and students who are given assignments in groups, (2) The effect of the interaction between the assignment method and student learning behavior on science learning outcomes, (3) Differences in results learning science between students who are given assignments individually and students who are given assignments in groups, for students who behave introverted, (4) Differences in science learning outcomes between students who are given assignments individually and students who are given assignments in groups, for students who behave extroverted. This research was conducted at SDN 1 Bone Raya using the 2 x 2 factorial design method. The results showed that: (1) there were differences in science learning outcomes for students who were assigned individual assignments and students who were assigned group assignments. This can be seen from the average score of Science Learning Outcomes, where XA1 = 17.50 is higher than XA2 = 15.33, (2) there is an interaction effect between the assignment method and learning behavior on science learning outcomes, (3 ) there are differences in learning outcomes. Science between students who were given assignments individually and students who were given assignments in groups for students who behaved introverted, as seen from the average score of science learning outcomes, where XA1B1 = 21.73 was greater than XA2B1 = 13.